2021
DOI: 10.31635/ccschem.020.202000311
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Conducting Polyoxometalates as Redox Electrolytes Synergistically Boosting the Performance of Self-Healing Solid-State Supercapacitors with Polyaniline

Abstract: Energy storage devices with high volumetric and gravimetric capacitance are in urgent demand due to the booming market of portable and wearable electronics. Using redox-active molecules as electrolytes is a strategy to improve the capacitance and energy density of solid-state supercapacitors (SCs). In this study, polyoxometalates (POMs) are applied as proton conductors and redox mediators in polyvinyl alcohol (PVA) electrolytes, which increase the capacitance of obtained SCs with polyaniline (PANI). H 3 PMo 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Ion-conducting polymer electrolytes have tremendous potential in a wide range of energy applications such as fuel cells, batteries, supercapacitors, and other energy storage and conversion devices. [1][2][3][4][5][6][7][8][9][10][11][12] Despite these promising applications, a key issue in polymer electrolytes is maximizing the ionic conductivity while simultaneously optimizing the mechanical performance, so as to prepare high conductive and high stable electrolyte membranes for practical use. 13 However, the facilitation of ion transport generally involves increasing the content of ionic groups or accelerating the segmental dynamics of polymer electrolytes, which inevitably causes the electrolyte membranes to become swollen or softened and thus sacrifice their mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Ion-conducting polymer electrolytes have tremendous potential in a wide range of energy applications such as fuel cells, batteries, supercapacitors, and other energy storage and conversion devices. [1][2][3][4][5][6][7][8][9][10][11][12] Despite these promising applications, a key issue in polymer electrolytes is maximizing the ionic conductivity while simultaneously optimizing the mechanical performance, so as to prepare high conductive and high stable electrolyte membranes for practical use. 13 However, the facilitation of ion transport generally involves increasing the content of ionic groups or accelerating the segmental dynamics of polymer electrolytes, which inevitably causes the electrolyte membranes to become swollen or softened and thus sacrifice their mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…The assembled supercapacitor showed 200% stretchability without any loss in performance and nearly 100% capacitance retention after 600 charging/discharging cycles. Cheng et al (2020) reported fabrication of H 3 PMo 12 O 40 loaded polyaniline electrodes with polyoxometalates‐PVA redox active electrolyte and polyaniline as current collector. The developed supercapacitor showed areal capacitance of 7.69 F/cm 2 at 0.5 mA/cm 2 with energy density of 0.53 mWh/cm 2 .…”
Section: Current Collector Materials For Multifarious Supercapacitorsmentioning
confidence: 99%
“…With the progress in supramolecular chemistry and synthetic chemistry, various self-healing polymers that are capable of healing damage by themselves to restore the mechanical and/or chemical properties have been Page 2 of 31 CCS Chemistry 3 successfully synthesized. [20][21][22][23] In addition, by combining self-healing polymers with functional materials, plenty of self-healing functional materials with superhydrophobicity, [24][25][26][27] antifouling, [28][29][30] electrical conductivity, [31][32][33][34] sensing, [35][36][37][38][39][40][41] and other functions [42][43][44][45][46][47][48][49][50] have been fabricated, significantly decreasing maintenance costs and promoting safety, reliability, and service life. The design and fabrication of self-healing materials with photothermal and water transportation capabilities that can repair their functions upon damage would be a judicious solution to increase the stability and service life of solar-driven interfacial evaporators.…”
Section: Introductionmentioning
confidence: 99%